2001
DOI: 10.1097/00000374-200105051-00033
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Alcohol Syndrome: An International Perspective

Abstract: This article represents the proceedings of a workshop at the 2000 ISBRA Meeting in Yokohama, Japan. The chairs were Kenneth R. Warren and Faye J. Calhoun. The presentations were (1) Epidemiological research on fetal alcohol syndrome (FAS) in the United States, by Philip A. May; (2) An overview of fetal alcohol syndrome in the Western Cape Province of South Africa, by Denis L. Viljoen and Ting-Kai Li; (3) Diagnostic perspectives of fetal alcohol and tobacco syndromes, by Harumi Tanaka; (4) FAS among pupils of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Women who drink alcohol during pregnancy are at a high risk of giving birth to children with physical, behavioral or cognitive developmental problems that can persist as lifelong disabilities called fetal alcohol spectrum disorders (FASD) (Warren et al 2001). Alcohol is a neurotoxic teratogen and many studies have shown that alcohol exposure has the potential to cause damage in different regions of the developing brain (Caetano et al 2006; Sawant et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Women who drink alcohol during pregnancy are at a high risk of giving birth to children with physical, behavioral or cognitive developmental problems that can persist as lifelong disabilities called fetal alcohol spectrum disorders (FASD) (Warren et al 2001). Alcohol is a neurotoxic teratogen and many studies have shown that alcohol exposure has the potential to cause damage in different regions of the developing brain (Caetano et al 2006; Sawant et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol misuse in pregnancy is also frequently associated with other conditions that can potentially increase the brain damage such as poor nutrition and smoking (Chen et al, 1998;Culverhouse et al, 2005;Gianoulakis, 1998;Lieber, 2003;Okosun et al, 2005;Raine, 2002). An extensive experimental and clinical literature shows that alcohol misuse results in fetal brain neurotoxicity associated with life-long behavioural, social and cognitive impairments (Chen et al, 2003;Goodlett et al, 2005;Guerri, 2002;Olney, 2004;Warren et al, 2001). Only a small proportion of children born to mothers with alcohol misuse fulfil the diagnostic criteria for Fetal Alcohol Syndrome (FAS), which include facial dysmorphology, growth retardation and central nervous system (CNS) dysfunction .…”
Section: The Effects Of Alcohol Misuse On Brain Growth and Plasticitymentioning
confidence: 99%
“…A large fraction of institutionalized children have FAS in Japan, Germany, and Russia, where research is ongoing (Warren et al, 2001).…”
Section: Fetal Alcohol Syndrome (Fas)mentioning
confidence: 99%